Google Classroom-based Online English Learning Material: The Practice and Perception - Sudaryani, Harlina (International Journal of English Language and Pedagogy, 2023)
The research aims to explore the Implementation of Google Classroom-based Online English Learning during Covid 19. It was descriptive qualitative research through a case study. The instruments used for collecting data were a questionnaire, interview, and observation. The researchers distributed questionnaires to a total 72 Accounting and Finance (AKL 1 and AKL 2) students of State Vocational High School 1 Purwodadi. However, only 12 participants were selected randomly to interview. This study found that Google Classroom-based Online English Learning is in line with existing learning steps where it offers numerous benefits for students. The English learning materials were helpful and interesting, the English learning materials given contained the latest materials, the English learning materials easily through Google Classroom, and English learning performance increased by learning English materials through Google Classroom